Use of Ceftolozane/Tazobactam in a Case of Septic Shock by Puerperal Sepsis - Mario Pezzi; Anna Maria Scozzafava; Anna Maria Giglio; Renata Vozzo; Patrizia Dina Casella; Simona Paola Tiburzi; Lucio Cosco; Mario Verre (Case Reports in Obstetrics and Gynecology)
Multiresistant bacteria infections cause widespread morbidity and mortality and lead to an increase in expenses for hospital stays and complications. We describe the case of a 27-year-old patient with puerperal sepsis after cesarean section due to Escherichia coli complicated by multiresistant Klebsiella ESBL-producing superinfection with septic shock and multiple organ dysfunction syndrome, successfully treated with ceftolozane/tazobactam.